(untitled) (Das Questões, 2021)
Swivelropy comes as a rhythmical movement. Swivel is a turn that requires co-action. It takes complexity to swivel. A -tropy ending is another kind of a turn that requires another kind of cooperation, that from an initial term to merge with. The text fuses both Nick Land’s and Evald Iliyenkov’s ideas and narratives into a new life and a new language. The language of Swiveltropism and a symbiotically induced life of Enola Yenkoni.